Sharity outreach programme : a promotional effect to inculate pro-social values amongst pre-school children in Singapore. - Chen, Julia Yuanzhi. (2008)
This project is on a five-day pilot programme, termed 'Sharity Week', held from February 9, 2004 to February 13, 2004 in a PCF pre-school centre.